2021
DOI: 10.3390/ijms22094406
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Properties of Polystyrene Nanoparticles with Different Diameters in Human Peripheral Blood Mononuclear Cells (In Vitro Study)

Abstract: With the ongoing commercialization, human exposure to plastic nanoparticles will dramatically increase, and evaluation of their potential toxicity is essential. There is an ongoing discussion on the human health effects induced by plastic particles. For this reason, in our work, we assessed the effect of polystyrene nanoparticles (PS-NPs) of various diameters (29, 44 and 72 nm) on selected parameters of oxidative stress and the viability of human peripheral blood mononuclear cells (PBMCs) in the in vitro syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 77 publications
0
20
0
3
Order By: Relevance
“…The synthesized A1-A6 color varied from dark red to brown, and the yield percentage ranged from 65 to 78%. Compounds 1 and 5 were prepared according to reported methods [24,25,29,30].…”
Section: Synthesis Of Azo-derivatives (A1-a6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized A1-A6 color varied from dark red to brown, and the yield percentage ranged from 65 to 78%. Compounds 1 and 5 were prepared according to reported methods [24,25,29,30].…”
Section: Synthesis Of Azo-derivatives (A1-a6)mentioning
confidence: 99%
“…The azo derivatives were prepared according to the reported methods. Compounds A1 and A5 were reported and prepared according to references [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…14,16 Exposure to a mixture of PS in micro and nano size was found to result in the deterioration of intestinal barrier function and cause gut microbiota dysbiosis in mice (reduction of microbial diversity). 17 So far, evidence has suggested that PS nanoplastics caused oxidative stress in human peripheral blood mononuclear cells, 18 toxicity in human lung epithelial cells 15 and DNA damage in monocytes. 19 Human lymphocytes, human B lymphoblastoids (Raji-B), human lymphoblast cells heterozygous at the thymidine kinase (TK6), and human foreskin fibroblast cells (Hs27) showed increased genotoxicity after treatment with PS nanoplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a series of studies on the chronic toxicity of MNP exposure has reported on potential risks that may be linked to various human health issues, including endocrine disturbances, reproductive toxicity [ 32 ], neurotoxicity, gastrointestinal toxicity, liver toxicity [ 14 ], cardiac fibrosis [ 33 ], pulmonary fibrosis, and even carcinogenesis [ 10 ]. Additionally, a line of proof has emerged of negative effects from exposure to PS MNPs and additives for blood plasma [ 34 , 35 ] and human health [ 36 ]. Based on scientific evidence, the serious risks of PS MNPs have been fully justified as a cause of cellular toxicity in mammals [ 37 ].…”
Section: Introductionmentioning
confidence: 99%